2012
DOI: 10.1590/s1678-77572012000400012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exogenous pigmentation on the optical properties of orthodontic elastic ligatures

Abstract: ObjectivesThe aim of this study was to assess the optical properties of orthodontic elastic ligatures under the influence of exogenous pigments contained in the daily diet. Material and methodsFor the analysis, colorless (clear) elastic segments (ORTHO Organizers, lot 660625A10) were used as received from the manufacturer, and were divided into 8 groups of 3 segments each. Each group was immersed in 200 mL of a solution containing a determined substance, as follows: distilled water (control group), Coca-Cola®,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 18 publications
2
27
2
1
Order By: Relevance
“…In the present study, tea caused significantly more discoloration than coffee. However, this disagrees with the findings of other studies carried out on elastomeric modules (Ardeshna and Vaidyanathan, 2009) (Ferrnandes et al, 2012) (Bhandari et al, 2014). The difference may be because of the different chemical composition and manufacturing technique between elastic chains and modules.…”
Section: Difference Between Companiescontrasting
confidence: 93%
See 1 more Smart Citation
“…In the present study, tea caused significantly more discoloration than coffee. However, this disagrees with the findings of other studies carried out on elastomeric modules (Ardeshna and Vaidyanathan, 2009) (Ferrnandes et al, 2012) (Bhandari et al, 2014). The difference may be because of the different chemical composition and manufacturing technique between elastic chains and modules.…”
Section: Difference Between Companiescontrasting
confidence: 93%
“…Therefore the comparison with other researches is not possible. However, previous researches on the discoloration of elastic modules also show a diversity in the intensity of discoloration caused by different media on the different brands of modules (Kim and Lee, 2009) (Ferrnandes et al, 2012) (Cavalcante et al,2013) (Bhandari et al,2014).…”
Section: Difference Between Companiesmentioning
confidence: 96%
“…22, 23, 31, 47, 48 In a few previous studies, coffee has been identified as the strongest staining agent among common beverages. 31, 32, 49 The Invisalign instructions for patients suggest that drinking coffee with the aligner in the mouth should be avoided. 50 The staining effect may be due to pigments, such as yellow dye in coffee and tea solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Elastomers are considered important adjuvant materials in orthodontic treatment and have many clinical applications 1,2 . This refers especially to esthetic elastomers used in adult patients who are highly demanding about the esthetic appearance of orthodontic appliances 3,4 . Elastomer chains can be classified as short, medium or long according to the distance between the links 5,6 .…”
Section: Introductionmentioning
confidence: 99%